PERFORMANSI PENGELOLAAN AGROFORESTRI DUKUH KECAMATAN PENGARON KABUPATEN BANJAR - Nur Weda Wani; Udiansyah Udiansyah; Hafizianor Hafizianor (Jurnal Sylva Scienteae, 2020)
Farmers have been  practicing traditional agroforestry for a long time. One of the agroforestry managers in dukuh is located in Pengaron Sub-district, South Kalimantan, which is a combination of fruit plants and empon-empon plants called dukuh. The study aims to analyze performance based on aspects of productivity, sustainability, fairness and efficiency. The benefits of providing information and input to be taken into consideration by forest management agencies and local governments in conducting dukuh development. The results of the Performance Study showed that Kertak Empat Village and Ati'im Village were very good with scores of 303 in Kertak Empat Village and 283 in Ati'im Village. Dukuh performance scores in the Kertak Empat Village are higher because the efforts made by Ati'im Village are still more intensive than the Kertak Empat dukuh, however the performance of the dukuh is equally good.Keywords: agroforestry, dukuh, performance